Транспорт - Клюшник Лариса Владимировна (Энциклопедия для детского сада, 2018)
Экземпляры: ДБ (20200831) / Инвентарный номер: 52824 / Цена: 108.90 / Сис.шифр: 39 / Авт.знак: К 52 / ГРНТИ: 73 / ББК: 39я2